A Study on the Effects of Cellular Mobile Networks on People in Tikrit City Based on Power Density Measurements and Calculations - Salih, A. A.; Saeed, A. T.; Saber, Z. R. (Engineering, Technology & Applied Science Research, 2019)
In this paper, the emitted electromagnetic waves (EMW) from different cellular mobile base stations (BSs) have been measured and calculated in order to study their effects on public health. Moreover, a comparison between the effect of radiated power from the BSs on people who live near them and those who live away has been made by using OpenSignal software and calculated theoretically. The values of power density for different cells were also calculated to compare them with the maximum permissible exposure limit-the acceptable range values of power density. The measurements were done in Tikrit City considering ten cells and various locations and distances. The results show that most of the power density and EMV for the tested cells are within the acceptable range. However, power density and EMV for two of tested cells have hurtful effects in the long term for people who live near the BSs.